2021
DOI: 10.1111/ene.14684
|View full text |Cite
|
Sign up to set email alerts
|

Headache at onset of first‐ever ischemic stroke: Clinical characteristics and predictors

Abstract: No studies have prospectively investigated headache at onset of first‐ever ischemic stroke along with a large concurrent control group. Our aims were to answer two important questions: (i) Are headaches at stroke onset causally related to the stroke, and what are their typical clinical characteristics? (ii) What etiology of stroke is associated with these headaches? The study population consisted of 550 patients (mean age = 63.1, 54% males) with first‐ever ischemic stroke and 192 control patients (mean age = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 11 publications
6
40
0
Order By: Relevance
“…According to our previous studies, 18.3% of the patients with TIA had sentinel headache within the last week before TIA [9], and 14.7% had sentinel headache before ischemic stroke [4]. We found that attacks of arrhythmia before a stroke and a history of atrial brillation were associated with this headache in stroke patients [4]. These data suggest that emboli can play an essential role in the development of this headache [4].…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…According to our previous studies, 18.3% of the patients with TIA had sentinel headache within the last week before TIA [9], and 14.7% had sentinel headache before ischemic stroke [4]. We found that attacks of arrhythmia before a stroke and a history of atrial brillation were associated with this headache in stroke patients [4]. These data suggest that emboli can play an essential role in the development of this headache [4].…”
Section: Discussionsupporting
confidence: 49%
“…We found that attacks of arrhythmia before a stroke and a history of atrial brillation were associated with this headache in stroke patients [4]. These data suggest that emboli can play an essential role in the development of this headache [4]. However, sentinel headache may be an alarming symptom in many other disorders (dissections, cerebral venous sinus thrombosis, etc.).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations